Crystal structure and Hirshfeld surface analyses, crystal voids, intermolecular interaction energies and energy frameworks of 3-benzyl-1-(3-bromopropyl)-5,5-diphenylimidazolidine-2,4-dione - Houda Lamssane; Amal Haoudi; Badr Eddine Kartah; Ahmed Mazzah; Joel T. Mague; Tuncer Hökelek; Youssef Kandri Rodi; Nada Kheira Sebbar (Acta Crystallographica Section E: Crystallographic Communications)
The title molecule, C25H23BrN2O2, adopts a cup shaped conformation with the distinctly ruffled imidazolidine ring as the base. In the crystal, weak C—H...O hydrogen bonds and C—H...π(ring) interactions form helical chains of molecules extending along the b-axis direction that are linked by additional weak C—H...π(ring) interactions across inversion centres. The Hirshfeld surface analysis of the crystal structure indicates that the most important contributions for the crystal packing are from H...H (51.0%), C...H/H...C (21.3%), Br...H/H...Br (12.8%) and O...H/H...O (12.4%) interactions. The volume of the crystal voids and the percentage of free space were calculated to be 251.24 Å3 and 11.71%, respectively, showing that there is no large cavity in the crystal packing. Evaluation of the electrostatic, dispersion and total energy frameworks indicate that the stabilization is dominated by the dispersion energy.